The Impact of Vaccination and Trade Openness on Child Mortality under Five - Hossein Panahi; Seyed Ali Aleemran (Tehran University of Medical Sciences, 2017)
Background and Aim: The present study aimed to assess the impact of trade openness and vaccination on child mortality under five because the mortality of under-five-year-old children is one of the most important indexes of health and development.  Materials and Methods: Using an Eviews6 software, this study is doing a causal-analytic approach by exhausting a Johansen-Juselius method over the period of first quarter of 1984 to forth quarter of 2013, in Iran. Results: Coefficients for each of the variables in the model were consistent with the theoretical bases. Based on the findings of the study, the increase of one unit in each of the variables of DTP vaccine and trade openness leads to the decrease of child mortality as much as 0.23 and 4.36 units, respectively. Also, the results based on error correction model indicate that in each period, about 0.04 of short-run imbalances is adjusted to achieve a long-term balance. Conclusion: Since the increase of vaccination and trade openness reduce the mortality of under-five-year-old children, it is suggested that the immunization of children be trained in all parts of the country so that we can achieve high rates of growth and development by the delivery of healthy factors of production to the society. Moreover, by increasing trade relations and dealings with other countries, we can prepare the grounds for the entry of new knowledge and medical equipment as well as health promotion and human development.